On the distribution of amino acid residues in transmembrane alpha-helix bundles. - Samatey, F A (1995)
The periodic distribution of residues in the sequence of 469 putative transmembrane alpha-helices from eukaryotic plasma membrane polytopic proteins has been analyzed with correlation matrices. The method does not involve any a priori assumption about the secondary structure of the segments or about the physicochemical properties of individual amino acid residues. Maximal correlation is observed at 3.6 residues per period, characteristic of alpha-helices. A scale extracted from the data describes the propensity of the various residues to lie on the same or on opposite helix faces. The most polar face of transmembrane helices, presumably that buried in the protein core, shows a strong enrichment in aromatic residues, while residues likely to face the fatty acyl chains of lipids are largely aliphatic.